2019
DOI: 10.1177/0284185118820049
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transhepatic biliary tract embolization using gelatin sponge

Abstract: Background Percutaneous biliary drainage (PTBD) is a necessary procedure in several benign and malignant conditions. After PTBD removal biliocutaneous fistula is a rare but potential complication. Different embolization agents have been used for transhepatic catheter tract embolization in the past, while there is only little experience using gelatin sponge for this procedure. Purpose To evaluate the feasibility and safety of PTBD tract embolization with gelatin sponge. Material and Methods Between July 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Based on the Newcastle-Ottawa scale assessment, 1 study was of high quality [ 15 ], 5 were of moderate quality [ 7 , 12 14 , 16 ], and 1 was of low quality [ 17 ]. Quality assessment is summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the Newcastle-Ottawa scale assessment, 1 study was of high quality [ 15 ], 5 were of moderate quality [ 7 , 12 14 , 16 ], and 1 was of low quality [ 17 ]. Quality assessment is summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The indication for PBI was mainly malign bile duct obstruction (not always specified) in all studies with 252/314 (80.3%, range: 61.9–100%). Patients with malign bile duct obstruction were mixed with patients with an underlying benign disease such as bile duct stones in 5 of 7 studies [ 7 , 12 , 14 16 ]. Only in two retrospective nonrandomised cohort studies, all patients showed a malign bile duct obstruction with concomitant ascites [ 13 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations